Muhasebe ve Finansman Öğretmenliği İçin Pedagojik Formasyon Eğitimi Alan Öğrencilerin Öğretmenlik Mesleğine ve Pedagojik Formasyon Eğitimine İlişkin Algıları - Ercan, Cuma (Muş Alparslan Üniversitesi, 2018)
The purpose of this study is to determine thelevel of perceptions related to the teaching profession and pedagogicalformation education of the students who took pedagogical formation to becomeaccounting and finance teachers. The study universe covers 101 students whoreceive pedagogical training at the Faculty of Education of Kilis 7 AralıkUniversity during the 2016-2017 academic year. Survey data were obtainedthrough questionnaires. The SPSS statistical program was used in the evaluationof the research results. The collected data were analyzed by applyingpercentage, frequency, arithmetic mean, and chi-square tests. According to theresults of the research, it was found that the students who had pedagogicalformation training to become accounting and finance instructors had a positiveperception about teaching profession and formation education. In addition, itwas determined that there was a meaningful difference in perception level ofstudents about formation education and teaching profession according to gender, age and department variables.

Bu çalışmanın amacı, muhasebe ve finansmanöğretmeni olmak için pedagojik formasyon eğitimi alan öğrencilerin öğretmenlikmesleğine ve pedagojik formasyon eğitimine ilişkin algı düzeylerinibelirlemektir. Çalışma evrenini, 2016-2017 eğitim - öğretim yılında Kilis 7Aralık Üniversitesi Eğitim Fakültesi’nde pedagojik formasyon eğitimi alan 101öğrenci oluşturmaktadır. Araştırma sonuçlarının değerlendirilmesinde SPSSistatistik programından yararlanılmıştır. Toplanan veriler; yüzde, frekans, aritmetik ortalama ve ki-kare testlerine tabi tutularak analiz edilmiştir.Araştırma sonuçlarına göre, muhasebe ve finansman öğretmenliği için pedagojikformasyon eğitimi alan öğrencilerin öğretmenlik mesleğine ve formasyoneğitimine ilişkin pozitif algıya sahip oldukları tespit edilmiştir. Bununyanında öğrencilerin formasyon eğitimi ve öğretmenlik mesleğine ilişkin algıdüzeylerinde cinsiyet, yaş ve bölüm değişkenlerine göre anlamlı bir farklılıkgösterdiği tespit edilmiştir.
The Perceptions Related to the Teaching Profession and Pedagogical Formation Education of the Students Who Are Taking Pedagogical Formation for Accounting and Finance Teaching
anemon
Keywords: Formation Education; Accounting and Finance; Teaching Profession; Muhasebe ve Finansman; Formasyon Eğitimi; Öğretmenlik Mesleği